Criteríos para la selección de un motor y controles eléctricos como prevención de riesgos en la industria - Quiñónez España, Miguel Geovanny (2010)
The electrical engines are one of the most important bases of the industry of nowadays. Its here it takes root in the importance to the moment to choose an adequate electrical engine with the correct criteria. The importance of this work is the incorporation of the electrical factors that concern an engine and his controls due to the repercussions of the new factors that they have presented already be for new equipments that have been added to the systems, as the different areas of utilization where nowadays they install electrical engines, the location of the engine, the type of charge that is going to move the engine and the control to protect, between others. Also inside each of the factors the relations are indicated between one and other one as well as what can happen in the case that exists some mistake or fault of some type inside the machine and even in the system that feeds it.